2010
DOI: 10.1111/j.1439-0507.2009.01703.x
|View full text |Cite
|
Sign up to set email alerts
|

Onychomycosis in Tehran: mycological study of 504 patients

Abstract: Onychomycosis is a common nail disorder resulting from the invasion of the nail plate by a dermatophyte, yeast or mould species and gives rise to some diverse clinical presentations. The purpose of the present study was to isolate and identify the causative fungi of onychomycosis in the population of Tehran, Iran. Nail samples from 504 patients with prediagnosis of onychomycosis during 2005 were examined both by direct microscopical observation of fungal elements in KOH preparations and in culture for the iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
24
3
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 20 publications
8
24
3
6
Order By: Relevance
“…Similar to other studies conducted in other regions of the world, our study confirmed that onychomycosis was the principal clinical presentation (56.9%) (30)(31)(32). Moreover, this form of infection has been found more often in female than male (33,34). This trend could be attributed to their activities because most of the affected females were working at home (defined as housewife in Table 3).…”
Section: Discussionsupporting
confidence: 89%
“…Similar to other studies conducted in other regions of the world, our study confirmed that onychomycosis was the principal clinical presentation (56.9%) (30)(31)(32). Moreover, this form of infection has been found more often in female than male (33,34). This trend could be attributed to their activities because most of the affected females were working at home (defined as housewife in Table 3).…”
Section: Discussionsupporting
confidence: 89%
“…The occurrence of 135 cases of Aspergillus nail infection in one year at the two medical mycology laboratories in Tehran is remarkable, and together with previous studies on onychomycosis in Tehran and in some other parts of the country, our data suggest that Aspergillus spp., mainly A. flavus, are somewhat commonly involved in NDM onychomycosis in Iran [8,10,18,27]. Unlike almost all studies performed in Iran, in our survey, the frequency of onychomycosis due to yeasts and NDMs exceeds the frequency of nail infections caused by dermatophytes [18]. This high occurrence was similar to that of Scherer et al who found a shift from dermatophytes to saprophytes as agents of nail infections [33].…”
Section: Discussionsupporting
confidence: 81%
“…Saprophytic onychomycosis can be caused by various fungi, including Scopulariopsis brevicaulis, Aspergillus spp., Fusarium spp., Acremonium spp., and Scytalidium spp. [6,7,10,16,18,28,37]. Some epidemiological studies indicate that Aspergillus is an emerging cause of toenail onychomycosis, and after Scopulariopsis it is the most common cause of nondermatophyte mold onychomycosis [13].…”
Section: Introductionmentioning
confidence: 99%
“…22 Cases of yeast infection of the nail were reported in the scientific literature by investigators evaluating onychomycoses in 504 patients in Tehran. 23 Onychomycoses were confirmed in 216 (42.8%) of the 504 cases analyzed. Those authors found yeast infections in 129/216 cases (59.7%), the most common causal agents being Candida albicans (n=42) and Candida spp (n=56).…”
Section: Discussionmentioning
confidence: 95%
“…Similar findings were also reported in Iran, Algiers, Canada and Italy, these investigators reporting the isolation of yeasts in fungal infections of the nail. 14,23,27,28 Investigators in Brazil conducted dermatophytic screening at the Araraquara Health Unit and found 15 cases of yeast infection (16.2%). 29 The results obtained in the present study, in which 23 cases of Candida yeast infection were detected in the toenails, a rate of 15.2%, are in agreement with the findings of the abovementioned investigators.…”
Section: Discussionmentioning
confidence: 99%